WHO 2022 landscape of papillary and chromophobe renal cell carcinoma - Lobo, João; Ohashi, Riuko; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Cree, Ian A.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Netto, George J.; Raspollini, Maria R.; Rubin, Mark A.; et al. (Histopathology, 2022)
The 5th edition of the WHO Classification of Tumours of the Urinary and Male Genital Systems contains relevant revisions and introduces a group of molecularly defined renal tumour subtypes. Herein we present the World Health Organization (WHO) 2022 perspectives on papillary and chromophobe renal cell carcinoma with emphasis on their evolving classification, differential diagnosis, and emerging entities. The WHO 2022 classification eliminated the type 1/2 papillary renal cell carcinoma (pRCC) subcategorization, given the recognition of frequent mixed tumour phenotypes and the existence of entities with a different molecular background within the type 2 pRCC category. Additionally, emerging entities such as biphasic squamoid alveolar RCC, biphasic hyalinising psammomatous RCC, papillary renal neoplasm with reverse polarity, and Warthin-like pRCC are included as part of the pRCC spectrum, while additional morphological and molecular data are being gathered. In addition to oncocytomas and chromophobe renal cell carcinoma (chRCC), a category of ‘other oncocytic tumours’ with oncocytoma/chRCC-like features has been introduced, including emerging entities, most with TSC/mTOR pathway alterations (eosinophilic vacuolated tumour and so-called ‘low-grade’ oncocytic tumour), deserving additional research. Eosinophilic solid and cystic RCC was accepted as a new and independent tumour entity. Finally, a highly reproducible and clinically relevant universal grading system for chRCC is still missing and is another niche of ongoing investigation. This review discusses these developments and highlights emerging morphological and molecular data relevant for the classification of renal cell carcinoma.
CRIS-Team Scopus Importer:2022-06-17
Keywords: chromophobe renal cell carcinoma; emerging entities; molecular pathology; papillary renal cell carcinoma; renal tumours